The genome sequence of the Orange Footman, Eilema sororcula (Hufnagel, 1766) [version 1; peer review: 2 approved] - Douglas Boyes; Owen T. Lewis (Wellcome Open Research, 2023)
We present a genome assembly from an individual male Eilema sororcula (the Orange Footman; Arthropoda; Insecta; Lepidoptera; Erebidae). The genome sequence is 729.4 megabases in span. Most of the assembly is scaffolded into 30 chromosomal pseudomolecules, including the Z sex chromosome. The mitochondrial genome has also been assembled and is 15.46 kilobases in length. Gene annotation of this assembly on Ensembl identified 21,093 protein coding genes.